2021
DOI: 10.3389/fsurg.2021.680930
|View full text |Cite
|
Sign up to set email alerts
|

Is Homeopathic Arnica Effective for Postoperative Recovery? A Meta-analysis of Placebo-Controlled and Active Comparator Trials

Abstract: Background: Homeopathic Arnica montana is used in surgery as prevention or treatment for the reduction of pain and other sequelae of surgery. Our aim was to perform a metaanalysis of clinical trials to assess efficacy of Arnica montana to reduce the inflammatory response after surgery.Method: We conducted a systematic review and metaanalysis, following a predefined protocol, of all studies on the use of homeopathic Arnica montana in surgery. We included all randomized and nonrandomized studies comparing homeop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…44 Although there are many studies reviewing the safety of homeopathic medications, the majority are small studies performed outside of the United States that examined specific therapies for specific maladies, and only one US study is specific to perinatal health. 35,[76][77][78] In a 2022 systematic review, Stub et al reported on 41 eligible observational studies and concluded that although adverse effects of homeopathic remedies are often reported and statistically significant (P < .0001), the proportion of adverse events among patients receiving conventional medicine and herbs was significantly higher (P = .0001). 79 A systematic review of published case reports of adverse effects of homeopathy by Posadzki et al concluded there was potential of both direct and indirect harms to patients.…”
Section: Safety Of Homeopathic Medicinesmentioning
confidence: 99%
“…44 Although there are many studies reviewing the safety of homeopathic medications, the majority are small studies performed outside of the United States that examined specific therapies for specific maladies, and only one US study is specific to perinatal health. 35,[76][77][78] In a 2022 systematic review, Stub et al reported on 41 eligible observational studies and concluded that although adverse effects of homeopathic remedies are often reported and statistically significant (P < .0001), the proportion of adverse events among patients receiving conventional medicine and herbs was significantly higher (P = .0001). 79 A systematic review of published case reports of adverse effects of homeopathy by Posadzki et al concluded there was potential of both direct and indirect harms to patients.…”
Section: Safety Of Homeopathic Medicinesmentioning
confidence: 99%